Receiving Healthcare Amidst Poverty During the COVID-19 Lockdowns: A Culture-Centered Interrogation. Issue 12 (15th October 2022) - Dutta, Mohan J.; Jayan, Pooja; Elers, Phoebe; Elers, Christine; Rahman, Md Mahbubur; Pokaia, Venessa
ABSTRACT: COVID-19 has exacerbated existing health inequalities globally. Guided by the culture-centered approach, this study examined perspectives and experiences of healthcare during two lockdowns in four marginalized contexts in Aotearoa New Zealand. The participants' narratives depicted dissatisfaction with the new modes of healthcare delivery, reporting longer waiting times, a preference for face-to-face delivery, language barriers, and issues with the limitations in support people attending appointments. This resulted in healthcare being delivered in a way that was not in keeping with the localized cultural norms of communication and collective support, further exacerbating existing health inequalities. Our findings suggest that public health interventions in response to COVID-19 within the context of healthcare delivery have the potential to further reify and reproduce exclusions and experiences of marginalization, with cultural marginalization reifying structural marginalization.